Quenched solid density functional theory method for characterization of mesoporous carbons by nitrogen adsorption. - Gor, Gennady Yu.; Thommes, Matthias; Cychosz, Katie A.; Neimark, Alexander V. (Carbon, 2012)
Quenched solid d. functional theory (QSDFT) model for characterization of mesoporous carbons using N2 adsorption is extended to cylindrical and spherical pore geometries. The kernels of theor. isotherms in the range from 0.4 to 50 nm are constructed accounting for different possible variations of the pore shapes in micropore and mesopore regions. The results of QSDFT method are illustrated with exptl. data on adsorption on novel CMK-3 and 3DOm carbons. The proposed method is recommended for pore size distribution calcns. for micro-mesoporous carbons obtained through various templating mechanisms. [on SciFinder(R)]
Keywords: mesoporous carbon pore size structure nitrogen adsorption quenched DFT